Parametric studies of capillary flow front velocity - Sulaiman, Maizan (2017)
Currently, active research on capillarity are being conducted in various fields such as biomedical, thermodynamic, electronic, hydrology, geology and aerospace. The study mainly focuses on the flow front velocity (Vff) for non ideal-case of capillary, spceifically to assist the designer of a system or process involved in fluid dynamic flow. Observation is conducted at difference inclination angle alpha (a) for both ascending and descending capillary flow. The real time computer screen displayed of 100* magnified 2D microscopy video of fluid flow front is analyzed to produce scattered exprimental data of the flow front velocity (Vf) against travelled distance (z ). The sufficient curve fitting result has been produced which the equation has negative power (-b) with an algebraic expressions of Vff = a z-b. It has been transformed into Vff = f(t) for the data of flow front velocity against time (t) for capillary flow related parameters investigation such as viscosity, diffusion, specific capillary geometry, inclination angle, deceleration, force due to the mass of retaining fluid and fingering flow type in the capillary fiber. The result of mathematical analysis such as an evaluation of variable values form curve equation, derivative and solving of parametric equations is used to establish the references to any process or system design for a micro machine.